1998
DOI: 10.1080/02652039809374713
|View full text |Cite
|
Sign up to set email alerts
|

Natural occurrence ofFusaviumtoxins in oats harvested during five years in an area of southwest Germany

Abstract: A total of 56, 56, 54, 51, and 55 oats samples used for feed production were collected randomly after the 1987, 1989, 1990, 1991 and 1992 crops, respectively, from farms located in an area of southwest Germany. Deoxynivalenol (DON), 3- and 15-acetyl-deoxynivalenol (3-, 15-ADON), nivalenol (NIV), fusarenon-X (FUS-X), T-2 toxin (T-2), HT-2 toxin (HT-2) and diacetoxyscirpenol (DAS) were determined by gas chromatography with mass selective detection (GC-MS), zearalenone (ZEA), alpha and beta-zearalenol (alpha-, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 19 publications
0
24
1
Order By: Relevance
“…The highest level of NIV was detected in one sample containing oats. It was clear from this work that contamination by DON and NIV is not only exclusive of corn but also of oat and wheat contents as some authors have reported for these ingredients (Mü ller et al, 1997(Mü ller et al, , 1998(Mü ller et al, , 2001Langseth and Rundberget, 1999;Schollenberger et al, 2002Schollenberger et al, , 2005a.…”
Section: Occurrence Of Don and Niv In Corn-based Foodsmentioning
confidence: 61%
“…The highest level of NIV was detected in one sample containing oats. It was clear from this work that contamination by DON and NIV is not only exclusive of corn but also of oat and wheat contents as some authors have reported for these ingredients (Mü ller et al, 1997(Mü ller et al, , 1998(Mü ller et al, , 2001Langseth and Rundberget, 1999;Schollenberger et al, 2002Schollenberger et al, , 2005a.…”
Section: Occurrence Of Don and Niv In Corn-based Foodsmentioning
confidence: 61%
“…It has a major effect on human and animal health and raise serious worldwide economic problems [5]. Several studies have reported high incidences of ZEN in several commodities frequently used in human food and animal diets [6][7][8]. ZEN is metabolized in liver at least into five metabolites; ZEN, α-zearalanol, β-zearalanol, α-zearalenol and β-zearalenol with α-zearalenol being the major ZEN metabolite in both ruminant and non-ruminant animals [9].…”
Section: Introductionmentioning
confidence: 99%
“…5,6) Co-contamination of Fusarium mycotoxins (TRs and ZEN) occurs worldwide in agricultural commodities and consumption of these has caused several outbreaks of intoxication in human and animal populations. [7][8][9][10][11][12] With the development of highly sensitive and simultaneous analytical methods, many reports regarding the co-contamination of Fusarium mycotoxins in processed cereal foods have been reported in Europe and North America, [13][14][15] but relatively little work is available for Asian countries despite these depending heavily on imported wheat and wheat-derived products. Thus, an accurate determination of processed food contaminated with these toxins is an urgent need for C 2010 The Pharmaceutical Society of Japan food supply.…”
Section: Iintroductionmentioning
confidence: 99%